Customized hybrid biomimetic hydroxyapatite scaffold for bone tissue regeneration. Issue 4 (28th December 2015) - Ciocca, L.; Lesci, I. G.; Mezini, O.; Parrilli, A.; Ragazzini, S.; Rinnovati, R.; Romagnoli, N.; Roveri, N.; Scotti, R.
Abstract: Three‐dimension (3D) scaffolds for bone tissue regeneration were produced combining three different phases: nanometric hydroxyapatite (HA) was synthesized by precipitation method and the crystals nucleation took place directly within collagen fibrils following a biologically inspired mineralization process; polycaprolactone was employed to give the material a 3D structure. The chemico‐physical analysis carried out to test the material's properties and composition revealed a high similarity in composition and morphology with biologically mineralized collagen fibrils and a scaffold degradation pattern suitable for physiological processes. The micro‐ computerized tomography (micro‐CT) showed 53.53% porosity and a 97.86% mean interconnected pores. Computer‐aided design and computer‐aided manufacturing (CAD‐CAM) technology was used for molding the scaffold's volume (design/shape) and for guiding the surgical procedure (cutting guides). The custom made scaffolds were implanted in sheep mandible using prototyped surgical guides and customized bone plates. After three months healing, scanning electron microscopy (SEM) analysis of the explanted scaffold revealed a massive cell seeding of the scaffold, with cell infiltration within the scaffold's interconnected pores. The micro‐CT of the explanted construct showed a good match between the scaffold and the adjacent host's bone, to shield the implant primary stability. Histology confirmed cell penetration and widely documented neoangiogenesis within the entire scaffold's volume. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 105B: 723–734, 2017.